Untangling the interaction between HP1α and the TERRA G-quadruplex : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry at Massey University, Manawatū, New Zealand - Roach, Ruby (Massey University, 2023)
Over 50 years ago the DNA double-helix structure was solved, revealing the code in which life is written. This set of instructions equates to three billion base-pairs, amounting to two metres in length, fitting into a human nucleus just six microns across. The stable yet dynamic structure that allows for the functional organisation of the genome is chromatin: a complex formed between DNA and proteins. Chromatin is delineated into two microscopically defined compartments: the less dense gene-rich euchromatin and the structurally compact gene-poor heterochromatin. Protective heterochromatin is constitutively maintained for telomere protection, chromosome segregation, DNA repair, and suppression of transposon activity. Essential for the propagation and maintenance of heterochromatin is Heterochromatin Protein 1α (HP1α), which is comprised of a chromodomain and chromoshadow domain separated by a disordered hinge. The histone code model proposes that HP1α is recruited to regions of heterochromatin by its chromodomain-mediated recognition of silent heterochromatin mark trimethylated lysine 9 of histone H3 (H3K9me3); however, this does not account for the specificity of HP1 paralogs, location-specific recruitment, or the contribution of RNA to heterochromatin formation. Here, Telomeric Repeat-containing RNA (TERRA), transcribed from the telomeres and shown to be involved in telomeric maintenance and stability, is investigated in its interaction with HP1α. The interaction with TERRA is proposed as a means for recruitment of HP1α to telomeres for chromosome end protection. Due to its guanine (G)-rich sequence, TERRA folds into a G quadruplex (G4), a topology distinctly different from canonical nucleic acid structures. The interaction between HP1α and TERRA is therefore investigated to establish the means of interaction between HP1α and a G4, and to examine the HP1α specificity towards TERRA G4s. This work showed that binding to TERRA is dependent upon multiple positively charged patches within the disordered hinge of HP1α, and is also affected by mimicking N-terminal phosphorylation, which alters the structure of HP1α. While the hinge of HP1α binds to a myriad of nucleic acid structures, the globular chromoshadow domain provided the specificity for the parallel G4 topology evident in TERRA. Solution structures of HP1α in complex with TERRA show that HP1α undergoes a conformational shift, becoming less flexible. These results show that noncanonical nucleic acid structures such as those formed by TERRA may act as determinants of HP1α function, serving as signposts in the genome for formation of protective heterochromatin. This biophysical study also further implicates non-canonical structures such as G4s as formidable regulators of genomic function.
Keywords: Chromosomal proteins; Heterochromatin; Non-coding RNA; Telomere; 310109 Proteomics and intermolecular interactions (excl. medical proteomics)